RARE CASES OF HYPERTROPHIC CARDIOMYOPATHY: VARIANTS AND CLINICAL OBSERVATIONS - V. Yu. Zimina; G. V. Mislitskaya; S. A. Sayganov; S. D. Dzakhova (Рациональная фармакотерапия в кардиологии)
Hypertrophic cardiomyopathy belongs to a group of hereditary diseases due to sarcomere gene mutation. This abnormality is characterized by the development of symmetric or asymmetric hypertrophy of left ventricular myocardium with its normal contractile function or hypercontractility. Authors provide a brief overview of variants of hypertrophic cardiomyopathy and phenocopies of this disease, when structural changes in the heart are not the result of classic sarcomere gene mutation. In patients with some phenocopies concentric left ventricular hypertrophy can transform into its dilatation with reduced contractility. Such variant of hypertrophic cardiomyopathy is presented in the first clinical observation. The second case shows that hypertrophic cardiomyopathy can be one of the symptoms of the disease with other reasons for poor outcome.